Influence of the Duration of the Second Stage of Labor on the Likelihood of Obstetric Anal Sphincter Injury. Issue 1 (March 2016) - Aiken, C.E.; Aiken, A.R.; Prentice, A.
Abstract : ( Birth . 2015;42(1):86–93) The long-term effects of obstetric anal sphincter injury can involve incontinence, pain, dyspareunia, and psychological trauma. The rate of this birth complication has increased dramatically in recent years in the United Kingdom, and while some studies have identified multiple risk factors, none have specifically examined the role that the duration of the second stage of labor might play.